Demographic profile of ear nose throat and head neck patients undergoing shortwave diathermy in a tertiary care centre of Punjab: a five-year study - Munjal, Manish; Teotia, Avkash; Kaur, Jatinder; Rishi, Porshia; Sidhu, Harjinder; Munjal, Shubham; Verma, Hitesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Short wave diathermy is a panacea in many otorhinolaryngology and head neck pathologies where either conservative therapeutic modality or surgical intervention has been undertaken. The profile of subjects who underwent short wave diathermy in a period of 5 year is discussed. Materials and Methods: 490 subjects undergoing short wave diathermy in the otorhinolaryngology and physiotherapy services of a tertiary care centre of Punjab were analyzed during a period of five years. The subjects were studied for their demographic profile. Results: Maximum patients 42.24% (207 patients) who underwent shortwave diathermy were in the middle age group (21-60 years). Females 62.04% (304 patients) outnumbered the males 37.95% (186 patients). Maximum sittings of male patients were 54 (13.91%) and for females were 47 (12.11%) during the period 2015-2016. Conclusion: Short wave diathermy is an effective pain therapy for inflammations of ear, nose neck and the maxillofacial region.